Intrinsic defect in B-lymphoblastoid cell lines from patients with X-linked lymphoproliferative disease type 1. I. Cell surface phenotype and functional studies - Shlapatska, L.M.; Kovalevska, L.M.; Gordiienko, I.M.; Sidorenko, S.P. (Experimental Oncology, 2014)
Background: Mutations in SH2D1A/DSHP/SAP gene are responsible for the onset of X-linked lymphoproliferative disease type 1 (XLP1) that have increased risk for B-cell lymphoma development. In XLP1 patients SAP deficient NK, NKT and CD8+ cytotoxic T cells are inefficient in eliminating EBV-infected proliferating B cells that may partially contribute to the lymphoma development. However, little is known about impairment of B cell characteristics in XLP1. Aim: To analyze the cell surface phenotype and functional characteristics of EBV-transformed B-lymphoblastoid cell lines from XLP1 patients (XLP B-LCLs) in comparison with conventional B-lymphoblastoid cell lines (B-LCLs). Methods: Studies were performed on SAP-negative B-LCLs T5-1, 6.16, RPMI 1788; SAP-positive B-LCL MP-1 and XLP B-LCLs IARC 739, XLP-D, XLP-8005. Cell surface immunophenotyping was performed using flow cytometry analysis. The level of apoptotic cells (Annexin V-binding), cell viability (MTT assay), and cell proliferation (trypan blue exclusion test) were evaluated in response to ligation of CD40, CD95, CD150 and IgM cell surface receptors. Results: A cell surface phenotype and functional features that distinguish XLP B-LCLs from conventional B-LCLs were revealed. XLP B-LCLs showed the upregulated level of CD20, CD38 and CD86 cell surface expression and downregulation of CD40, CD80 and CD150 expression. The major functional differences of XLP B-LCLs from conventional B-LCLs concern the modulation of CD95 apoptosis via CD40 and CD150 receptors and unresponsiveness to proliferative signals triggered by CD40 or colligation of BCR with CD150. Conclusion: The data suggest that the B-LCL from XLP1 patients have an intrinsic defect that affects cell activation, apoptosis, and proliferation. Key Words: B-lymphoblastoid cell lines, X-linked lymphoproliferative disease type 1, CD150, CD40, CD95, apoptosis.